Impact of the Siewert Classification on the Outcome of Patients Treated by Preoperative Chemoradiotherapy for a Nonmetastatic Adenocarcinoma of the Oesophagogastric Junction. (10th September 2015) - Moureau-Zabotto, Laurence; Teissier, Eric; Cowen, Didier; Azria, David; Ellis, Steve; Resbeut, Michel
Abstract : The aim of the study is to analyze the impact of the Siewert classification on the pathological complete response (pcR), pattern of failure, and general outcome of patients treated, by preoperative chemoradiotherapy and surgery for an gastroesophageal junction adenocarcinoma (OGJA). From 2000 to 2008, the charts of 68 patients were retrospectively reviewed. Tumor staging reported was UST1/T2/T3/T4/unknown, respectively, n = 1/7/54/5/1 patients, and N0/N1/unknown, respectively, n = 9/58/1 patients. Patients received primary external-beam radiotherapy with concurrent chemotherapy followed by surgical resection (Siewert I: upper oesogastrectomy; Siewert II/III: total gastrectomy with lower oesophagectomy). Overall survival (OS), overall relapse rate (ORR), cumulative rate of local (CRLR), nodal (CRNR), and metastatic (CRMR) relapse, and their prognostic factors were retrospectively analyzed. Median follow-up was 77.5 months. Median OS was 41.7 ± 5.2 months. The 3-year ORR was 48%. Using univariate analysis ORR was significantly increased for patients with Siewert II/III compared to Siewert I tumors (27.3% versus 62%, p = 0.047 ). Siewert I tumors had also statistically lower CRNR and CRMR compared to Siewert II/III tumors (0/9.1% versus 41.3/60.2% resp., p = 0.012 ), despite an equivalent cumulative rate of local relapse and pathological complete response rate between the three groups. For OGJA treated with preoperative CRT and surgery, ORR and CRMR were lower for patients with Siewert I tumors in comparison with Siewert II/III tumors.